STANDARDIZED HIGHER ORDER THINKING SKILLS’ ASSESSMENT IN ENGINEERING MECHANICS: A TRADITIONAL LITERATURE REVIEW AND FUTURE RESEARCH DIRECTIONS - Maharani, Salma; Arthur, Riyan; Soeprijanto, Soeprijanto (Universitas Labuhanbatu, 2025)
Purpose – This study aims to examine the need to develop assessment instruments for higher-order thinking skills in teaching Engineering Mechanics in Vocational High Schools under the Construction and Property Technology Expertise Program and explore directions for future research.Methodology – This study employs a Traditional Literature Review approach to summarize, analyze, and synthesize over 100 scholarly sources from Google Scholar and Scopus databases from 2016 to 2025. The analysis uses keywords such as higher-order thinking skills (HOTS), assessment, Engineering Mechanics, vocational high schools (SMK), and test theory.Findings – The review findings indicate that the teaching of Engineering Mechanics in vocational high schools (SMK) has not yet optimally incorporated higher-order thinking skills (HOTS). Teachers tend to use test items based on classical test theory, which are limited in accurately measuring students' analytical and problem-solving skills. The assessment approaches employed have yet to consider the alignment of test items with students' characteristics.Contribution – This study contributes to the development of more accurate HOTS-based Engineering Mechanics assessment instruments through the application of modern test theory, while also enhancing the quality of teaching and assessment in Vocational High Schools specializing in Construction and Property Technology to better align with industry demands.